(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Forest soil antagonistic bacteria Bacillus carotarum was isolated and tested for optimum antimicrobial metabolite production. Maximum antimicrobial metabolite production was found at temperature 30°C and pH 7.0 and on Ist day of incubation at stationary condition. The medium consisting of beef extract - 0.3%, peptone - 0.5% and NaCl - 0.05%, was screened out as a suitable medium for maximum antimicrobial production supplemented individually with four carbon sources of which starch was found as the best carbon source. The active agent was best extracted with petroleum ether. Homogeneity of the crude bioactive metabolites were also tested by paper chromatographic analysis where a single type of bioactive metabolite was found with a Rf value of 0.94 in the solvent system n- butanol: acetic acid : water = 4 : 1 : 5 . The antimicrobial spectrum of the metabolite was wide and showed activity against Shigella dysenteriae (AE14612), Salmonella typhi(AE14296), Vibrio cholerae (A214748), Pseudomonas aeruginosa (CRL, ICDDR’ B), Bacillus cereus (BTCC19), and Bacillus subtilis (BTTC17). The Chittagong Univ. J. B. Sci. 8(1&2): 01-10, 2013